Obstacles of Applying Total Quality Management Principles in Banking Sector, Gezira State, Sudan (2021) - Masaad, Osman Tagelsir (Gezira Journal of Economic and Social Sciences; مجلد 12 عدد 2 (2021), 2022)
Preface : Competition in providing high-quality service became a goal sought by service organizations, including banks. That was after service quality became the basic standard of institutional success and guaranteed their survival and continuity in the market. This study aimed at identifying the most important obstacles that confront the application of TQM principles in the Sudanese banking sector from the point of view of banks’ employees . Method : The study relied on primary data collected through a structured questionnaire compassing a random sample of 100 individuals working in the banking sector in Gezira state. The study used descriptive analysis utilizing frequency tables, in addition to inferential statistics using factor analysis and Fisher Exact Test in the Chi-squared procedure in SPSS program version 20 . Results : The study found a number of obstacles that prevent the application of TQM principles in Sudanese banks. Their rank came according to their contribution in the total variance of quality obstacles, as follows: organizational obstacles; obstacles relating to administrative leaders; obstacles relating to the dissemination of quality culture; obstacles relating to employees. The study also found that there were no statistically significant differences in the level of obstacles of applying TQM principles in the banking sector attributed to the variables of job rank, academic qualification, and years of experience except those related to the educational level of the bank employee. Recommendation : The study recommended the necessity of confronting these obstacles by banks and to find the required solutions for them.